Validity of an Inertial Measurement Unit System to Assess Lower-limb Kinematics during a Maximal Linear Deceleration - Alastair R. Jordan; Howie J. Carson; Brett Wilkie Wilkie; Damian J. Harper (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2021)
This study examined the validity of an inertial measurement unit system for measuring lower-limb joint kinematics during linear decelerations. A male team athlete (age 36 years, stature 1.75 m, mass 80.0 kg) performed multiple linear decelerations, following 20 m runs at 50%, 75% and 100% self-perceived effort. Inertial measurement unit sensors were strapped to lower-limb segments and retroreflective markers were adhered to the lower-limbs for 3D optical motion analysis. Ground contact time, foot to centre of mass displacement (foot-COM), peak and minimum angle, mean angular velocity and range of motion at the ankle, knee and hip during the contact phases of each deceleration were determined. Measures were valid if a very large correlation (r ≥ 0.7) and small bias (effect size < 0.6) were evident. Following 50% effort, ground contact time, foot-COM and most hip and knee kinematics were valid. Ground contact time, foot-COM and knee flexion velocity and range of motion were valid following 75% efforts. Ground contact time and knee flexion velocity were valid following 100% effort. Therefore, the inertial measurement unit system tested can be used to assess temporal-spatial parameters during a deceleration regardless of the preceding effort, and hip and knee kinematics following low intensity running.